The Quality of e-Ridesharing: Are the e-Ridesharing Passengers Satisfied? - Alif Azhari Ismail; Safwana NurWidad Safri; Nor Asmalina Mohd Anuar; Zurinawati Mohi (Politeknik Negeri Bandung, 2023)
The rise of ridesharing e-booking applications in Malaysia with their interesting features and characteristics seems to give a huge impact on the transportation industry. However, there are several issues pertaining to security, safety, legality, and regulations. Three primary service quality dimensions of e-ridesharing, which are considered fit and suitable in the context of the current study, are identified, including app quality, interaction quality, and physical environment quality. 487 questionnaires were used for data analyses. The subdimensions were verified using an exploratory factor, and regression analysis was conducted further. The result indicates that e-ridesharing service quality dimensions, which include app quality, interaction quality, and physical environment quality, are able to improve passengers’ satisfaction and re-ride intention. The findings are expected to help increase the quality of services offered by the service providers and contribute to the body of knowledge which can be replicated in the various service industries.